Prospects for Improving a Credit Mechanism in the Agricultural Sector of the Ukraine Economy - Serge KOLOTUKHA; Nataliia GVOZDEJ; Liudmyla CHVERTKO; Tetiana KORNIIENKO; Oksana VINNYTSKA (Communications of International Proceedings, 2020)
The necessity of optimization of financial and credit support for the development of the agro-industrial sector of the economy has been substantiated. The ways of activating bank lending to agricultural enterprises by improving the mechanism for determining interest rates for loans, introducing mortgage lending in agriculture, using credit incentives for the rational use of land and insuring credit risks. The expediency of improving the mechanism of state support for agricultural producers has been determined both through budget financing of national programs and through lending from the budget. The assessment of the current state of state financial assistance to the subjects of agricultural production is carried out, measures are proposed to improve the existing mechanisms of financial and credit support and stabilize the situation in the agricultural sector of the economy.
Keywords: Agriculture; Agricultural Producers; Financial Support; Credit Support; Credit Relations; Mortgage Crediting; Land Bank; Credit Risk; Risk Insurance.